Organizational Servant Leadership: A Systematic Literature Review for Implications in Business - Avinash Pawar; Khortum Sudan; Satini Satini; Denok Sunarsi (International Journal of Educational Administration, Management, and Leadership, 2020)
The leadership of servants is a new research area linked to ethics, virtues, and morality. As critics debate whether this new leadership theory is significantly distinct, viable, and valuable for organizational success, scholars are currently looking for publication outlets. The objective of this research was to identify empirical studies that explored the theory of servant leadership by involving a sample population to evaluate and synthesize the mechanisms, results, and impacts of servant leadership. Therefore, we were trying to provide an evidence-informed answer to how the ship's servant leader works and how can we apply it? To synthesize research in a systematic, transparent and reproducible way, we conducted a sys-thematic literature review (SLR), a methodology adopted from the medical sciences. A disciplined screening process resulted in 39 appropriate studies of the final sample population. The synthesis of these empirical studies revealed: (a) there is no consensus on the definition of servant leadership; (b) the theory of servant leadership is being studied in a variety of contexts, cultures, and themes; (c) researchers use multiple measures to explore servant leadership, and (d) servant leadership is a viable theory of leadership that helps organizations and enhances us. This research helps to develop the leadership of servants. Theory and exercise. Furthermore, this research contributes to the methodology for conducting SLRs in the field of management, highlighting an efficient method for thematically mapping and holistic viewing of new research topics. By offering suggestions for future research, we conclude.